Effect of the Application of a Coating Native Potato Starch/Nopal Mucilage/Pectin on Physicochemical and Physiological Properties during Storage of Fuerte and Hass Avocado (Persea americana) - Choque Quispe, David (2022)
The avocado fruit is an agro-industrial product with high export demand in Peru due to its sensory and nutritional qualities, which can be affected during storage. The study aimed to evaluate the effect of the application of a coating formulated with potato starch (Solanum tuberosum ssp andigena), nopalmucilage (Opuntia ficus indica), and pectin on the physicochemical and physiological properties during the storage of Fuerte and Hass avocados. Samples were taken in their harvest state from the plantation in “Occobamba”, which is cultivated by the Avocado Producers Association in Chincheros, Apurímac, Peru. Physicochemical properties (titratable acidity, pH, total soluble solids) and physiological properties (weight loss, firmness, and color L* a* b*) were determined during 20 days of storage at 20 C. The elaborated films present high transparency and low aw values. In the coated avocado of the Hass and Fuerte varieties, acidity and total soluble solids decreased significantly (p-value < 0.05) during the storage time. Weight loss and firmness of coated fruits decrease to a lesser extent. Luminosity L*, color index, and color variation showed better attributes for the coated samples. The use of coatings made with potato starch, nopal mucilage, and pectin allows the physicochemical and physiological properties of avocado fruits to be maintained for a longer time during storage.